Impact of discontinuing 5 years of enzyme replacement treatment in a cohort of 6 adults with hypophosphatasia: A case series - Cheryl Rockman-Greenberg; Robert Josse; Mira Francis; Aziz Mhanni (Bone Reports, 2022)
Asfotase alfa is a human recombinant enzyme replacement therapy for hypophosphatasia. We describe 6 adults who were treated with asfotase alfa for 61–68 months in a clinical trial (NCT01163149), after which asfotase alfa was discontinued for 15–48 months. The patients experienced clinical deterioration and, when treatment was restarted, showed improvement. Patients with hypophosphatasia should be closely monitored if asfotase alfa is stopped as clinical decline is likely. Clinical practice guidelines are needed.